2012
DOI: 10.1002/anie.201107333
|View full text |Cite
|
Sign up to set email alerts
|

[(Cp‐R)M(CO)3] (M=Re or 99mTc) Arylsulfonamide, Arylsulfamide, and Arylsulfamate Conjugates for Selective Targeting of Human Carbonic Anhydrase IX

Abstract: Enhanced receptor selectivity: carbonic anhydrase inhibitors are relevant for both cancer diagnosis and therapy. Combining non-radioactive Re compounds with their radioactive (99m)Tc homologs enables the use of identical molecules for therapy and imaging (theragnostic). The syntheses and in vitro evaluation of [(Cp-R)M(CO)(3)] (Cp=cyclopentadienyl, M=Re, (99m)Tc) with R being a highly potent carbonic-anhydrase-targeting vector is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
64
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(66 citation statements)
references
References 42 publications
2
64
0
Order By: Relevance
“…Some of these compounds demonstrated nanomolar affinities for the pharmaceutically relevant isozymes h ‐CA IX and h ‐CA XII, much higher affinity than that of acetazolamide, which is a benchmark organic inhibitor for CAs. A co‐crystal structure of a Re complex with h ‐CA II showed that the deprotonated nitrogen of the sulfonamide group bound to the catalytically active Zn center, and the [CpRe(CO) 3 ] moiety took part in hydrophobic interactions with Phe131, Leu198, and Pro202 . Biological activity and structure–activity relationships (SARs) for metallocenes functionalized with the sulfonamide pharmacophore through triazole, triazole–ester, triazole–amide, amide and urea linkers have been reported.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Some of these compounds demonstrated nanomolar affinities for the pharmaceutically relevant isozymes h ‐CA IX and h ‐CA XII, much higher affinity than that of acetazolamide, which is a benchmark organic inhibitor for CAs. A co‐crystal structure of a Re complex with h ‐CA II showed that the deprotonated nitrogen of the sulfonamide group bound to the catalytically active Zn center, and the [CpRe(CO) 3 ] moiety took part in hydrophobic interactions with Phe131, Leu198, and Pro202 . Biological activity and structure–activity relationships (SARs) for metallocenes functionalized with the sulfonamide pharmacophore through triazole, triazole–ester, triazole–amide, amide and urea linkers have been reported.…”
Section: Introductionsupporting
confidence: 63%
“…Ac o-crystal structure of aR e complex with h-CA II showed that the deprotonated nitrogen of the sulfonamide group bound to the catalytically activeZ n center,a nd the [CpRe(CO) 3 ]m oiety took part in hydrophobic interactions with Phe131,L eu198,a nd Pro202. [22] Biological activity and structure-activity relationships (SARs) for metallocenes functionalized with the sulfonamide pharmacophore through triazole, triazole-ester,t riazole-amide, amide and urea linkers have been reported. These compounds showed moderate to good inhibitory activity in vitro and some examples demonstrated high selectivity for cancer-associated CA IX and CA XII compared to off-target CA Iand CA II.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of isozymes of carbonic anhydrase that are overexpressed in certain tumors has also encouraged researchers to create new sulfonamide compounds with applications such as targeting by luminescence or γ-emission [33, 34]. The publication of the crystal structure of carbonic anhydrase with the metal complex, Cp R Re (CO) 3 (R = arylsulfonamide) bound to the zinc ion at the active site highlights the interest in this area [35, 36]. Although 4-aminofluorescein is not fluorescent, the parent fluorescein molecule finds heavy use in cellular imaging, and the development of Re(CO) 3 + based luminescent molecules has been a goal of many research groups [1113].…”
Section: Introductionmentioning
confidence: 99%
“…18 This was recently conrmed with an X-ray structure of an aryl-sulfonamide-bearing Ru pianostool complex incorporated within hCA II. 19,20 However, this latter proved catalytically inactive for a variety of transformations. Herein we report on our efforts to create an articial transfer hydrogenase based on the incorporation of a catalytically active iridium pianostool complex within hCA II, Fig.…”
Section: Introductionmentioning
confidence: 99%